2010
DOI: 10.1007/s00244-010-9526-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Veterinary Pharmaceutical Ivermectin in Indoor Aquatic Microcosms

Abstract: The effects of the parasiticide ivermectin were assessed in plankton-dominated indoor microcosms. Ivermectin was applied once at concentrations of 30, 100, 300, 1000, 3000, and 10,000 ng/l. The half-life (dissipation time 50%; DT50) of ivermectin in the water phase ranged from 1.1 to 8.3 days. The lowest NOECcommunity that could be derived on an isolated sampling from the microcosm study by means of multivariate techniques was 100 ng/l. The most sensitive species in the microcosm study were the cladocerans Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…It is also of note that water samples were collected and analyzed immediately, whereas under the field conditions runoff water is exposed to light, and these photosensitive compounds can rapidly degrade to biologically inactive compounds. The half‐life of tetracyclines ranges between 16 and 41 d (Loftin et al, 2008), whereas ivermectin photodegradation is much faster, with a half‐life of about 8 d (Boonstra et al, 2011). Thus, the runoff water concentrations of the studied pharmaceuticals in the flood‐irrigated rangelands are expected to be lower than what is reported here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also of note that water samples were collected and analyzed immediately, whereas under the field conditions runoff water is exposed to light, and these photosensitive compounds can rapidly degrade to biologically inactive compounds. The half‐life of tetracyclines ranges between 16 and 41 d (Loftin et al, 2008), whereas ivermectin photodegradation is much faster, with a half‐life of about 8 d (Boonstra et al, 2011). Thus, the runoff water concentrations of the studied pharmaceuticals in the flood‐irrigated rangelands are expected to be lower than what is reported here.…”
Section: Resultsmentioning
confidence: 99%
“…Data from Boonstra et al (2011), Wikler et al (2006); Kotze et al (2004); Loftin et al (2008), and Sanderson and Thomsen (2009).…”
Section: Chemical Structure and Selected Properties Of The Studied Phmentioning
confidence: 99%
“…This may explain positive effects of highly toxic pesticides (especially chlorpyrifos + cypermethrin) on some plankton groups (including higher survival rates of relatively larger plankton), especially during the wet season. The highly toxic insecticide abamectin may have exerted direct negative effects on plankton (especially maxillopods); several studies (Ali et al 1997;Tišler & Eržen 2006;Boonstra et al 2011;Braun et al 2012) have reported high lethal toxicity of abamectin on micro-crustaceans. However, the abundance of copepods may also have been diminished through increased predation by macro-invertebrates, ultimately traceable to negative effects of abamectin on fishes (Figures 2 and 4).…”
Section: Variation Of Organism Concentrations Of Different Plankton Gmentioning
confidence: 99%
“…An understanding of which and to what extent processes are affected may also give insight into responses of more complex systems (Benton et al 2007;Daam and Van Den Brink 2007;Boonstra et al 2011). But besides offering higher statistical power when compared with larger and/or more complex microcosms, the impacts on system processes can be quantified as interactions change.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it possible to assess the effects of environmental contaminants on species interactions, indirect effects, and effects at the population and community levels. An understanding of which and to what extent processes are affected may also give insight into responses of more complex systems (Benton et al 2007;Daam and Van Den Brink 2007;Boonstra et al 2011).…”
Section: Discussionmentioning
confidence: 99%